2018
DOI: 10.1007/s00442-018-4159-6
|View full text |Cite
|
Sign up to set email alerts
|

Strong specificity and network modularity at a very fine phylogenetic scale in the lichen genus Peltigera

Abstract: Identifying the drivers and evolutionary consequences of species interactions is a major goal of community ecology. Network-based analyses can provide mathematical tools to detect non-random patterns of interactions, and potentially help predicting the consequences of such patterns on evolutionary dynamics of symbiotic systems. Here, we characterize the structure of a lichen network at a very fine phylogenetic scale, by identifying the photosynthetic partners (i.e., cyanobacteria of the genus Nostoc) of lichen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 122 publications
(173 reference statements)
6
36
0
Order By: Relevance
“…We thus calculated two widely used network metrics (i.e., modularity and nestedness), over a gradient of sampling effort ranging between ~ 50 and our full 1,026 thalli dataset. Confirming what we had found in prior analyses on the section Polydactylon of the genus Peltigera (Chagnon et al, ), we found that modularity and nestedness did vary with sampling effort, but with trends that increasingly diverged from random expectations as sampling effort increased (Figure ). In other words, further sampling would have only strengthened our conclusions about network structure.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…We thus calculated two widely used network metrics (i.e., modularity and nestedness), over a gradient of sampling effort ranging between ~ 50 and our full 1,026 thalli dataset. Confirming what we had found in prior analyses on the section Polydactylon of the genus Peltigera (Chagnon et al, ), we found that modularity and nestedness did vary with sampling effort, but with trends that increasingly diverged from random expectations as sampling effort increased (Figure ). In other words, further sampling would have only strengthened our conclusions about network structure.…”
Section: Resultssupporting
confidence: 90%
“…We assembled a dataset of Peltigera-Nostoc interaction pairs summing up all information from the literature for which we could confidently assess the identity of the Peltigera species and Nostoc phylogroups or haplotypes (Chagnon et al, 2018;Lu et al, 2018;Magain, Miadlikowska, Goffinet, et al, 2017a;Magain, Miadlikowska, Mueller, et al, 2017b;Magain et al, 2018;Miadlikowska et al, 2014Miadlikowska et al, , 2018O'Brien, Miadlikowska, & Lutzoni, 2005;O'Brien, Miadlikowska, & Lutzoni, 2013;Pardo De la Hoz et al, 2018). The total dataset consisted of 1,026 thalli, or interaction pairs, representing 155 Peltigera species and 95 Nostoc phylogroups or haplotypes (Tables S1 and S2).…”
Section: Sample Acquisition and Interaction Network Inferencementioning
confidence: 99%
See 3 more Smart Citations